A Systematic Review of Root Canal Filling Materials for Deciduous Teeth: Is There an Alternative for Zinc Oxide-Eugenol?. (17th October 2010) - Barja-Fidalgo, Fernanda; Moutinho-Ribeiro, Michele; Oliveira, Maria Angelina Amorim; Oliveira, Branca Heloísa de
Abstract : The aim of this systematic review was to determine whether there is a root canal filling for deciduous teeth equally or more effective than zinc oxide-eugenol cement (ZOE). Six clinical trials selected for inclusion were independently reviewed by two researchers. Only two showed statistically significant different success rates between the test and the control groups. One found that an iodoform paste with calcium hydroxide (IP + Ca ) performed better than ZOE, and the other found that ZOE performed similarly toIP + Ca . The other four studies compared ZOE with an iodoform paste (IP), a calcium hydroxide cement( Ca ( OH ) 2 ), orIP + Ca . In these trials, the success rates in the ZOE groups were slightly lower than in the other groups. There seems to be no convincing evidence to support the superiority of any material over ZOE, and both ZOE andIP + Ca appear to be suitable as root canal fillings for deciduous teeth.